MS 2627-2:2025 Detection of porcine DNA - test method - part 2: cosmetics - Yahya, Padillah; Borhan, Fakheezah; Othman, Nurul I'zzati; Tulimin, Azmaniza; Ishak, Nooratiny; Mohd Saad, Shukriah; Ibrahim, Siti Aminah; Mohd Hassan, Fadilah; Wan Abdullah, Fariza; Sudarto, Liza; Al-Saari, Nurhidayu; Hanafi, Nor Izyani; et al. (Jabatan Standard Malaysia, 2025)
This document describes the adapted and modified methods for the qualitative detection of porcine deoxyribonucleic acid (DNA) in cosmetics. It is applicable to physical nature of cosmetics (solid, semi-solid and liquid). The real-time polymerase chain reaction (qPCR) technique is used for the identification and confirmation of the presence of porcine DNA. The described method has been optimised for some cosmetic matrices; nonetheless, owing to the unique characteristics of each cosmetic under analysis, certain procedural adjustments may be requisite within the laboratory setting. In such cases, the laboratory may proceed with the modifications, provided validation studies had been carried out.